NodeMCU Microcontroller Based Electrical Energy Consumption Monitoring System - Purnama Arifian, Raafi' Yanuar; Irawan, Denny (Indonesian Vocational Research Journal, 2024)
Electricity is one of human needs in everyday life. Based on these problems, this research was carried out, with the aim of creating a prototype to record electrical power loads and display the amount of electricity consumption in rupiah levels to monitor electrical energy consumption and convert it into rupiah. To conduct this research, the author used observational research methodology or field study and literature study. In this research, it is necessary to pay attention to understanding how to think and how to carry out the results of thinking according to scientific steps. By conducting this research, researchers hope to be able to find out data on daily electrical energy consumption and prevent electricity waste.